Pengembangan Aplikasi People Management dalam Software Development dengan Pendekatan Project Management Antipatterns - Reza Aprillia Arshanty; Umi Sa'adah; Desy Intan Permata Sari; Maulidan Bagus Afridian Rasyid (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
Human factor in software development process is one of the determinants of success of a project, regardless of the technology and tools used. In practice, many project managers do not have any dataset about hard skills and soft skills of their members. This led the software development project team to be trapped in an antipatterns irrational management situation. Based on several main factors that cause software development project failures, a mitigation plan is needed to assist the project manager in managing human resources in their team. The mitigation plan that can be done is to develop people management applications based on principles of Project Management Antipatterns. This research proposes new modeling in the form of applications for people management in software development with the Project Management Antipatterns approach. The results given are in the form of mapping the developer team to the relevant task based on hard skills and soft skills possessed. Besides, this application also provides results in the form of treatment recommendations that can be done to the team to increase productivity and reduce the potential risks arising from the diagnosis of poor practice. The approach used is proven to be able to increase overall team productivity. The refactored solution also proved effective in reducing the value of antipatterns from one sprint to the next.